Burden and impact of takotsubo syndrome in myasthenic crisis: A national inpatient perspective on the under-recognized but potentially fatal association. (15th January 2020) - Desai, Rupak; Abbas, Shabber A.; Fong, Hee Kong; Lodhi, Muhammad Uzair; Doshi, Rajkumar; Savani, Sejal; Gangani, Kishorbhai; Sachdeva, Rajesh; Kumar, Gautam
Abstract: Background: Patients with myasthenia gravis (MG) remain at a higher risk of developing takotsubo syndrome (TS), particularly during a myasthenic crisis (MC) event. The prevalence of MC-associated TS and its impact on subsequent in-hospital outcomes have not been explored previously. Methods: We queried the National Inpatient Sample (NIS) databases (2007–2014) using weighted data and ICD-9 CM codes to evaluate the prevalence of MC-associated TS, demographics, comorbidities and inpatient outcomes of TS secondary to MC vs. other triggers. Results: The nationwide prevalence of MC-associated TS was 0.3% (175/56, 472). Of all 156, 506 TS encounters, MC was present in 0.11% (n = 175) of cases. The groups were comparable in terms of demographics (median age 68–73 years, Caucasian >70%, females >80%). In comparison to non-MC TS, MC-associated TS demonstrated a higher frequency of coexisting diabetes and a lower frequency of smoking. The MC-TS cohort experienced significantly higher rates of all-cause mortality [8.6% vs. 4.7%, p = 0.014, unadjusted (OR1.91, p = 0.017) and adjusted (OR1.82, p = 0.038)] and complications including respiratory failure, the need of intubation/mechanical ventilation, and arrhythmia. The MC-TS cohort had fewer routine discharges and frequent transfers. The median stay was 6 days longer (10 vs. 4 days) and median hospital charges per admission were nearly $100, 000 higher ($133, 999 vs. $38, 367) with MC-associated TS. Conclusions: This population-based analysis revealed a 15 times greater prevalence of secondary TS following MC as compared to the general inpatient population, a nearly 2 times higher odds of all-cause mortality, and significantly higher resource utilization in MC-associated TS as compared to TS triggered by other etiologies. Highlights: Prevalence of TS in MC was 15 times greater than the prevalence in general population. Of all secondary TS, MC was found to be a trigger in 0.11% of cases. MC-TS showed significantly higher mortality & complications as compared to non MC-TS. MC- TS showed fewer routine discharges and frequent transfers to other facilities. MC-TS showed higher LOS and hospital charges as compared non MC-TS.